Strategi Pariwisata Terintegrasi Berbasis Sentralitas Spasial Pada Desa Wisata Di Kabupaten Sleman - Daeng Noerdjamal; Fiona Yonanda Putri; Huriyah Dzikriyatul Ainunnajah; Maulidina Ihza Almayda; Riki Subianto; Darmawan, Hariyadi Darmawan (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
Tourism village is one of Indonesia's tourism development priorities program, but its development is often faced several issues, one of its issues is the offer of similar tourist attractions between tourism villages. Likewise, the issues faced by Sleman Regency in the development of its tourism village. Thus, it is necessary to have an integrated tourism strategy to create a cooperation network between tourism villages. The purpose of this study is to identify and interpret connectivity and relationships between tourism villages, followed by formulating an integrated tourism strategy based on spatial centrality in tourism villages in Sleman Regency. The method used is a quantitative research method with a survey approach through checklists and interviews. The data analysis technique uses spatial network construction analysis of gravity models and Geographic Information System (GIS). The results of this study indicate the operationalization framework of an integrated tourism strategy based on seven aspects of the significance of integrated tourism according to Oliver and Jenkins (2001) and a hierarchy of classification of tourism village roles based on spatial centrality.